Structure and optical properties of sputter deposited pseudobrookite Fe2TiO5 thin films - Ngo, Hai Dang; Pucci, Annemarie (CrystEngComm, 2018)
Iron(III) titanates are composed of earth-abundant elements and are attracting rapidly growing interest as highly promising candidates for solar-energy as well as optoelectronics applications. In this article, we report on the successful synthesis of pseudobrookite Fe2TiO5 thin films with RF sputtering followed by post-deposition annealing in air. The chemical composition, crystal structure, surface morphology, and optical properties of the films were characterized both experimentally and theoretically. The film was confirmed to be single phase and exhibited a highly crystalline orthorhombic structure with a preferential crystal orientation of (131) with excellent adhesion on both glass and silicon substrates, indicating that an epitaxial substrate is not required. Dielectric functions from spectroscopic ellipsometry and density functional theory (DFT) also provide a good understanding of the optical characteristics of the films.